Formation and recovery of secondary forests in India: a particular reference to western Ghats in South India - Bhat, D.M.; Murali, K.S.; Ravindranath, N.H. (2001)
This paper analyses the underlying causes of secondary forest formation and recovery in India, particularly the Western Ghats region of south India, from precolonial times to the present. In the pre colonial period, hunter gatherers, shifting cultivators and settled cultivators were the dominant users of forest land, with some limited timber felling by local chieftains and kings. There was limited secondary forest formation following extractive activities by the communities and the State. The State takeover of forests for commercial timber exploitation during the colonial period, the resulting alienation of local community rights, and the over exploitation of forest products from limited areas accessible to the community were key factors in the large-scale formation of secondary forests. In the post independence period, the diversion of forestland for other purposes and industrial pressures led to deforestation and forest degradation. Currently, forest cover is relatively low and primary forests exist only in hilly tracts. However, forest cover has stabilised in spite of increasing population density. With the passing of the Forest Conservation Act of 1980, which banned forest clearing, forest conversion pressures were reduced. During the last decade, the rehabilitation of degraded secondary forests and the regeneration of secondary forest on degraded land by communities have contributed to the stabilisation of forest cover. The paper hypothesises that joint management of forests by governments and communities, as well as policies to reduce dependence on fuelwood, may have paved the way for this favourable development.